Hungarian Religion, Romanian Blood: A Minority's Struggle for National Belonging, 1920-1945 - Davis, R. Chris (University of Wisconsin Press, 2018)
Intro -- Contents -- List of Illustrations -- Preface -- Dramatis Personae -- Introduction -- 1. Demography Is Destiny: People, Space, and Nation -- 2. The Sacred: Religion, Kulturkampf, and Catholic-Orthodox Polemics -- 3. The Profane: A True Science of the Nation and People -- 4. Certifiably Romanian: Codifying National Belonging -- 5. Resettlement "Home": Solving Demographic Crises -- 6. The Cry of Blood: The Csangos Recertified -- Conclusion -- Glossary -- Notes -- Bibliography -- Index